EFFECTIVENESS OF CAESAREAN SECTION CLINICAL PATHWAY TOWARDS HOSPITAL LENGTH OF STAY: A SYSTEMATIC REVIEW - Maria Wahyu Daruki; Atik Nurwahyuni; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Improving quality and efficiency in hospital services can be done by using Clinical Pathway (CP). CP can decrease the hospital length of stay and cost. In indonsia, the increasing number of Caesarean Section (SC) affects to the Length of Stay (LOS) in hospital. This study aims to examine the effectiveness of clinical pathway in caesaren section to length of stay in the hospital. Methods: This study was a systematic review used PRISMA guidelines. Data obtained from Electronic journal databases Pubmed and ProQuest that published between 2014 until 2019 and used English language. By using keywords such as clinical pathway, childbirth labor, and length of stay to find the relevant journal. Results: The search found out 4,937, studies from 2 journal databases. The articles that not suitable with the criteria inclusion must be exclude. Totally, 6 studies were analyzed in this study. 1 study explained the affect of increasing length of stay in the National Health Insurance, 2 studies mentioned that CP was not affected to the length of stay in hospital and 3 studies mentioned that CP was reduced the length of stay in hospital. Conclusion: Clinical pathway in Caesarean section can reduced the length of stay in hospital. The hospital should implement the clinical pathway in caesarean section to increase the quality of hospital service and reduce the cost. Keywords: Clinical Pathway, Childbirth Labor, Length of Stay, Casearean Section